The efficacy of prophylactic intravenous granisetron in preventing post anaesthesia shivering in gynaecological patients undergoing surgery under general anaesthesia - Adania A,; Ooi, Joanna Su Min (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Post-anaesthetic shivering is one of the commonest complications during emergence from general anaesthesia with the rate of occurrence between 5 to 65%. It increases oxygen consumption and carbon dioxide production resulting in delayed recovery from anaesthesia and other adverse events. Granisetron is one of the drugs used to prevent post-anaesthetic shivering. This prospective, double-blind and randomised control study compared the efficacy of prophylaxis IV granisetron at 2 mg and 3 mg doses in preventing post-anaesthetic shivering. There were 104 patients, ASA I and II scheduled for elective open gynaecological surgery recruited and randomised into 2 groups: Group A and B, receiving 2 and 3 mg of IV granisetron, resepectively. Intravenous anaesthetic drugs were administered and tracheal intubation was facilitated by muscle paralysis. Patients’ baseline and periodic tympanic core temperatures were measured perioperatively. The incidence and severity of shivering were assessed postoperatively using Wrench Scoring Classification whereby Group A and B had 8.3% and 16.7% of incidence, respectively, in which they were not statistically significant (p = 0.199). All patients from both groups who shivered experienced Grade 1 shivering except for one patient who registered a Grade 2 in Group B. None of our patients had Grade 3 or 4 shivering postoperatively. No one experienced nausea or vomiting in the recovery area. Prophylactic IV granisetron of 2 mg and 3 mg were equally effective in reducing the incidence and severity of post-anaesthetic shivering in gynaecological patients undergoing surgery under general anaesthesia with no unpleasant side effects.